Karyotype description of five species of Trichomycterus (Teleostei: Siluriformes: Trichomycteridae) - Sato, Luciana Ramos [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Sociedade Brasileira de Genética, 2004)
Trichomycteridae is a family of small catfish which are widely distributed throughout Southern Central America and South America. The present study showed that the cis-Andean species Trichomycterus florensis, Trichomycterus sp. aff. Trichomycterus itatiyae, Trichomycterus reinhardti, Trichomycterus davisi and Trichomycterus auroguttatus had 2n = 54 chromosomes (42 metacentric, 10 submetacentric and 2 subtelocentric), with T. reinhardti, T. auroguttatus and T. sp. aff. T. itatiyae exhibiting only one chromosome pair with silver-stained nucleolus organizer regions (NORs). The cytogenetic data suggest the existence of at least two groups of species in the cis-Andean representatives of the genus Trichomycterus. In the first group the first metacentric pair is considerably larger than the second metacentric pair and the NORs occur in the pericentromeric position of the short arm of a large submetacentric pair while in the second group the first and second metacentric pairs are about the same size and larger than the other metacentric pairs and the NORs are located in the pericentromeric position of the long arm of a large metacentric pair. The relative conservatism of the karyotype of the cis-Andean Trichomycterus species contrasts with the wide diversification observed in the trans-Andean species, reinforcing the hypothesis that the genus is not monophyletic.
Keywords: chromosome evolution; NOR banding; fish